Peer Support Amplifies the Benefits of Psychological Help-Seeking on Adolescent Well-Being in Indonesia’s Collectivist Culture - Abdul Kholiq; Nirma Latifatul Khafidhoh; Ebony Melzak (Pamomong: Journal of Islamic Educational Counseling, 2025)
Indonesian adolescents are increasingly exhibiting reduced engagement in psychological help-seeking. This study investigates the moderating role of Peer Support (PS) in the relationship between Psychological Help-Seeking (PHS) and Psychological Well-Being (PWB), with the hypothesis that PS amplifies the positive effects of PHS. A cross-sectional survey was administered to 1,385 adolescents (510 males, 875 females; M = 14.2, SD = 2.1) in Central Java using stratified random sampling. Three validated self-report instruments were employed: the 42-item PWB scale (α = .91), whose six-factor structure was confirmed via CFA in the present sample (N = 1,374; CFI = .962, RMSEA = .042); the 14-item PHS scale (α = .83); and the 23-item PS scale (α = .88). Hierarchical regression controlling for gender and age showed that PHS significantly predicted PWB (β = .35, p < .001, R² = .28). The interaction term PHS × PS accounted for an additional 3% of the variance (ΔR² = .03, p = .002). Simple slope analyses indicated that the positive association between PHS and PWB was stronger among adolescents with high PS (+1 SD; β = .53) than among those with low PS (−1 SD; β = .17), confirming the strengthening effect of peer support. Findings highlight the role of peer support in moderating the relationship between PHS and PWB in collectivist contexts, supporting the use of peer networks to enhance the effectiveness of help-seeking. Practically, these results encourage school counselors to prioritize peer-support training and integrate peer-facilitator programs to strengthen adolescents’ help-seeking and psychological well-being.